Mandapa (pillared hall) of the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
The Mahakal Temple mandapa (pillared hall) has a depiction of dikapalas (deities for cardinal directions). Kuber is one of them who is portrayed with four arms. He holds a money bag in his upper hand, a kamandalu (water pot) in his lower left hand, and a gada (mace) in his lower right hand. At the base of the niche, Kubera’s Mount Airavat is carved.